2019
DOI: 10.1177/2515690x19828325
|View full text |Cite
|
Sign up to set email alerts
|

Yoga-Specific Enhancement of Quality of Life Among Women With Breast Cancer: Systematic Review and Exploratory Meta-Analysis of Randomized Controlled Trials

Abstract: Physical activities during and after cancer treatment have favorable psychosocial effects. Increasingly, yoga has become a popular approach to improving the quality of life (QoL) of women with breast cancer. However, the extant synthetic evidence on yoga has not used other exercise comparison conditions. This meta-analysis aimed to systematically assess yoga-specific effects relative to any other physical exercise intervention (eg, aerobics) for women with breast cancer. QoL was the primary outcome of interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 41 publications
1
37
0
4
Order By: Relevance
“…Fatigue is a common symptom in cancer survivors [24], and indeed PA is an effective treatment for post-cancer fatigue especially if supervised [25,26]. BC survivors who are experiencing fatigue should have access to a holistic and comprehensive approach to management of fatigue including PA supervised by an exercise physiologist, cognitive and behavioural strategies, and mindfulness and yoga-based interventions which show promise in alleviating post-BC fatigue [27,28]. Our findings also suggest a gap in translation of the evidence on exercise as a treatment for post-cancer fatigue with women who cited fatigue as a barrier to PA possibly not being referred to exercise physiologists, which might be derived from their lower self-reported PA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue is a common symptom in cancer survivors [24], and indeed PA is an effective treatment for post-cancer fatigue especially if supervised [25,26]. BC survivors who are experiencing fatigue should have access to a holistic and comprehensive approach to management of fatigue including PA supervised by an exercise physiologist, cognitive and behavioural strategies, and mindfulness and yoga-based interventions which show promise in alleviating post-BC fatigue [27,28]. Our findings also suggest a gap in translation of the evidence on exercise as a treatment for post-cancer fatigue with women who cited fatigue as a barrier to PA possibly not being referred to exercise physiologists, which might be derived from their lower self-reported PA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue is a common symptom in cancer survivors [24], and indeed PA is an effective treatment for post-cancer fatigue especially if supervised [25,26]. BC survivors who are experiencing fatigue should have access to a holistic and comprehensive approach to management of fatigue including PA supervised by an exercise physiologist, cognitive and behavioural strategies, and mindfulness and yogabased interventions which show promise in alleviating post-BC fatigue [27] [28]. Our ndings also suggest a gap in translation of the evidence on exercise as a treatment for post-cancer fatigue with women who cited fatigue as a barrier to PA possibly not being referred to exercise physiologists, which might be derived from their lower self-reported PA levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the most prevalent complementary therapies used in breast cancer care, seems to be as effective as other exercise modalities for improving the QoL of women with breast cancer [598]. Wei, et al [599] reported significant improvement in lymphedema status, range of shoulder motion and spinal mobility after an 8-week yoga intervention [599]. Although, yoga could not improve HRQoL in patients with colorectal cancer [600] but research supports that yoga is a promising intervention for reducing fatigue and sleep disturbances in this patient group [601].…”
Section: Alternative Therapies and Mind-body Interventionsmentioning
confidence: 99%